Pathobiology of cigarette smoke-induced invasive cancer of the renal pelvis and its prevention by vitamin C. (2018) - Ganguly, Shinjini; Chandra, Ayan; Chatterjee, Indu B.
Graphical abstract: Highlights: Cigarette smoke causes invasive urothelial cancer (pT1) in the renal pelvis. The initial pathogeneses are oxidative damage followed by aberrant EGFR activation. Oral vitamin C supplementation holistically prevents the tumor formation. Abstract: Urothelial cancer of the renal pelvis (CRP) is predominantly associated with cigarette smoking. However, the molecular pathogenesis of initiation and progression of cigarette smoke (CS)-induced CRP is unknown. Majority of CRP is high grade and high stage at presentation and has a high recurrence rate even after surgery. Earlier we reported that prolonged treatment (24 weeks) of a guinea pig model with p-benzoquinone (p-BQ), a product of CS in vivo, produced carcinoma in situ in the renal pelvis, a noninvasive cancer. Since CS is known to induce invasive cancer, we investigated the effect of CS exposure to the guinea pigs. We observed that CS exposure for a short period (18 weeks) produced invasive tumor (pT1). pT1 was confirmed by immunohistochemistry showing increased immunoexpression of nuclear p53 indicating p53 mutation, aberrant CK20, increased Ki-67 and uniformly negative labeling of CD44. As observed earlier with p-BQ treatment, the initial events of CS exposure were oxidative damage and apoptosis that was followed by persistent signaling through EGFR and MAP kinase pathway. CS exposure also caused hyperphosphorylation of pRb, activation of cyclin E and cell cycle deregulation leading to infiltration of epithelial cells in lamina propria of the renal pelvis resulting in pT1 tumor. Oral supplementation of vitamin C (30 mg/kg guinea pig/day) inhibited oxidative damage and apoptosis and holistically prevented the tumor formation. We consider that our preclinical findings on the intake of adequate vitamin C, along with intense advice for cessation of smoking, will be helpful for the prevention of CS-induced CRP in smokers.